2000
DOI: 10.1042/0264-6021:3470781
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C activation by acidic proteins including 14-3-3

Abstract: 14-3-3 proteins may function as adapter or scaffold proteins in signal transduction pathways. We reported previously that several 14-3-3 isotypes bind to protein kinase C (PKC)-zeta and facilitate coupling of PKC-zeta to Raf-1 [van der Hoeven, van der Wal, Ruurs, van Dijk and van Blitterswijk (2000) Biochem. J. 345, 297-306], an event that boosts the mitogen-activated protein kinase (ERK) pathway in Rat-1 fibroblasts. The present work investigated whether bound 14-3-3 would affect PKC-zeta activity. Using reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 23 publications
0
28
0
1
Order By: Relevance
“…Spatial and temporal control of PKC signalling is also influenced via interaction with adaptor/scaffolding proteins that anchor the PKCs to various intracellular locations in the cell. A multitude of adaptor proteins that influence PKC function have been characterised, including A-Kinase Anchoring Proteins (AKAPs) [15,16], Receptors for Activated C Kinases (RACKs) [17,18] and 14-3-3 proteins [19,20]. Termination of PKC signalling is best described for cPKCs and nPKCs.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Spatial and temporal control of PKC signalling is also influenced via interaction with adaptor/scaffolding proteins that anchor the PKCs to various intracellular locations in the cell. A multitude of adaptor proteins that influence PKC function have been characterised, including A-Kinase Anchoring Proteins (AKAPs) [15,16], Receptors for Activated C Kinases (RACKs) [17,18] and 14-3-3 proteins [19,20]. Termination of PKC signalling is best described for cPKCs and nPKCs.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Moreover, 14-3-3 proteins have been implicated also in Ras/MAPK cascade signaling in vertebrates (Fantl et al 1994;Li et al 1995) and during pseudohyphal development in S. cerevisiae (Roberts et al 1997). Finally, vertebrate 14-3-3 proteins were shown to inhibit or activate protein kinase C (PKC), which is involved in many signaling processes (Toker et al 1990;Isobe et al 1992;Tanji et al 1994), and to stimulate the interaction between PKC and the mitogenstimulated Raf1 kinase that controls cell growth (Van Der Hoeven et al 2000).…”
mentioning
confidence: 99%
“…This protein family can either positively modulate enzyme activity, in the cases of serotonin Nacetyltransferase (Obsil et al 2001) and Protein Kinase C (Van Der Hoeven et al 2000), or negatively modulate activity, such as with CaM-kinase kinase (Davare et al 2004). Specifically in the ERK pathways, 14-3-3 does not impact the activity of MEK (Shimizu et al 1994), but it has been reported to stimulate the enzyme upstream from MEK, Raf (Freed et al 1994) ) and associates with other upstream kinases in the pathway (Yamamori et al 1995).…”
Section: Discussionmentioning
confidence: 99%